2021
DOI: 10.15517/psm.v19i2.46278
|View full text |Cite
|
Sign up to set email alerts
|

La asimetría entre receptores y donantes como problema sanitario. Exploración de la aceptación o la negativa familiar a la donación de órganos y tejidos

Abstract: La investigación tuvo por objetivo indagar los conocimientos, las actitudes y las creencias de familias involucradas en procesos de decisión sobre la donación de órganos. Se llevó a cabo un estudio de carácter cualitativo con un diseño de tipo descriptivo e interpretativo. Participaron 14 grupos familiares de potenciales donantes y se elaboró un guion temático para el desarrollo de entrevistas a 10 de ellos que aceptaron y a 4 que rechazaron la donación. De acuerdo con los resultados, las decisiones se vieron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
0
2
Order By: Relevance
“…Consequently, a lower donation rate is observed in the Colombian context. In contrast, a 2017 study in Argentina demonstrated that 60% of the total potential donors eventually became utilized donors (29). When comparing this result with the utilized donor rate in our study (10.1%), the significance of persisting in strategies to promote donation in our country is underscored (30).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Consequently, a lower donation rate is observed in the Colombian context. In contrast, a 2017 study in Argentina demonstrated that 60% of the total potential donors eventually became utilized donors (29). When comparing this result with the utilized donor rate in our study (10.1%), the significance of persisting in strategies to promote donation in our country is underscored (30).…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, a study at a transplant center in Colombia between 2007 and 2016 determined a utilized donor rate of 27.3%, which is higher compared to the current study (31). In conclusion, a lower rate of utilized donors was identified when compared to global, regional, and local studies (28,29,31).…”
Section: Discussioncontrasting
confidence: 53%